Development and Verification of Microclimate Control System for Enhanced Driver Comfort and Safety Based on Skin Resistance Measurements - Kollárik Rastislav; Vitázek Ivan; Janča Jan; Jukić Željko (Acta Technologica Agriculturae)
This study deals with the design and construction of a device that enhances driver comfort and safety by automatically adjusting the microclimate in the vehicle cabin based on real-time skin resistance measurements. Using electrodes attached to driver‘s skin and an Arduino microcontroller, the system monitors and evaluates skin conductivity and adjusts heating, ventilation, and air conditioning (HVAC) settings accordingly. Experimental verification in laboratory conditions demonstrated device‘s functionality in changing microclimate parameters. Preliminary results suggest a potential correlation between baseline skin resistance values and the magnitude of observed changes in response to ambient conditions. Subjects with lower baseline skin resistance (≤100,000 Ω) showed smaller changes compared to those with higher baseline resistance (≥100,000 Ω). The current results are graphically processed as the course of skin resistance changes depending on the changing parameters of microclimate.